Does ownership affect the impact of taxes on firm behavior? Evidence from China - Clemens Fuest; Li Liu (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Does ownership affect the way firms react to corporate taxation? This paper exploits key features of recent corporate tax reforms in China to shed light on the differential impact of taxation on firms under different ownership regimes including private, collectively owned and state owned companies. Employing a difference-in-difference estimation approach, we find that the increase in the deductibility of wage costs in 2006 has led to a sizable increase of wages per worker in private firms and an even larger increase in collective-owned enterprises. In contrast, there is no significant wage response in state owned enterprises. The decrease in the statutory tax rate for domestic firms since 2008 has induced collectivley owned enterprises and private firms to reduce debt while there is no significant response SOEs. Our results also suggest that the 2008 reform has reduced tax induced investment round tripping through Hong Kong, Macao and Taiwan.
urn:nbn:de:bsz:180-madoc-388772
Keywords: 330